Living Qur’an and Living Hadith in Contemporary Islamic Studies: An Epistemological Analysis of Authority, Reception, and the Legitimacy of Religious Practices - Berliana, Diva Queen; Iliyin, Iklima; Muthmainnah, Zulfa Syarifah (Al-Karim: International Journal of Quranic and Islamic Studies, 2026)
This study examines the epistemological relationship between the Living Qur’an and the Living Hadith within the framework of contemporary Islamic studies. Although both approaches emphasize the manifestation of sacred texts in social life, comparative studies that systematically analyze their differences and interconnections remain limited. This article aims to analyze the forms of authority, reception, and legitimacy that characterize both paradigms and to explain how their interaction shapes contemporary Muslim religious practices. This study employs a qualitative descriptive method based on library research. Data were collected from primary and secondary sources on Living Qur’an and Living Hadith studies and analyzed comparatively through an epistemological approach. The analysis focuses on three aspects: the source of authority, the pattern of social reception, and the legitimacy of religious practices derived from the Qur’an and Hadith. The findings show that the Living Qur’an is grounded in the authority of divine revelation, which is sacred, stable, and transcendent. Consequently, the reception of the Qur’an tends to be more homogeneous and directly legitimized by the sacred status of the text. In contrast, the Living Hadith is rooted in the historical authority of the Prophet, mediated through isnad, scholarly interpretation, and local cultural adaptation. This makes hadith-based practices more diverse, contextual, and dependent on social negotiation. Despite these differences, the two paradigms are complementary. The Qur’an provides the theological and moral foundation, while the Hadith operationalizes and contextualizes these values in everyday life. Their interaction produces dynamic religious practices that reflect both normative commitments and social realities. Contribution: This study contributes to contemporary Islamic studies by offering a comparative epistemological framework for understanding the relationship between sacred texts and lived religious experience. It also enriches the methodological development of interdisciplinary, empirical, and contextual approaches in Qur’anic and Hadith studies.